International spillovers from US forward guidance to equity markets - Richhild Moessner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We quantify the international spillovers of explicit FOMC policy rate guidance used as an unconventional monetary policy tool at the zero lower bound of the policy rate on international equity markets, considering equity indices of both advanced and emerging economies. We find that explicit FOMC policy rate guidance announcements at the zero lower bound led to higher equity prices in a number of advanced and emerging economies. Moreover, we find that equity indices of economies with lower sovereign ratings rose by more, consistent with the risk-taking channel of monetary policy.
Keywords: E52; E58; G15; 330